Big bad bubble [videorecording (DVD)] - Rubin, Adam, 1983-; Salmieri, Daniel, 1983-; Heyborne, Kirby (Dreamscape Media, LLC, 2014)
An ordinary bubble may seem pretty harmless, but to the monsters of La La Land, however, a fragile, shimmering bubble is an object of terror, and when the frightening habits of bubbles are detailed by a fear-mongering monster, Yerbert, Froofle, and Wumpus run away and cry. But with encouragement from the narrator and the viewer, the three learn to confront their fears and triumph over the bubbles.